Disruption of Yeast Forkhead-associated Cell Cycle Transcription by Oxidative Stress - Shapira, Michael (The American Society for Cell Biology, 2004)
The effects of oxidative stress on yeast cell cycle depend on the stress-exerting agent. We studied the effects of two oxidative stress agents, hydrogen peroxide (HP) and the superoxide-generating agent menadione (MD). We found that two small coexpressed groups of genes regulated by the Mcm1-Fkh2-Ndd1 transcription regulatory complex are sufficient to account for the difference in the effects of HP and MD on the progress of the cell cycle, namely, G1 arrest with MD and an S phase delay followed by a G2/M arrest with HP. Support for this hypothesis is provided by fkh1fkh2 double mutants, which are affected by MD as we find HP affects wild-type cells. The apparent involvement of a forkhead protein in HP-induced cell cycle arrest, similar to that reported for Caenorhabditis elegans and human, describes a potentially novel stress response pathway in yeast.